In the Words of Frederick Douglass : Quotations from Liberty's Champion - Douglass, Frederick, 1818-1895 (Book collections on Project MUSE., 2012)
Frederick Douglass, a runaway Maryland slave, was witness to and participant in some of the most important events in the history of the American Republic between the years of 1818 and 1895. Beginning his long public career in 1841 as an agent of the Massachusetts Anti-Slavery Society, Douglass subsequently edited four newspapers and championed many reform movements. An advocate of morality, economic accumulation, self-help, and equality, Douglass supported racial pride, constant agitation against racial discrimination, vocational education for Blacks, and nonviolent passive resistance. He was the only man who played a prominent role at the 1848 meeting in Seneca Falls that formally launched the women's rights movement. He was a temperance advocate and opposed capital punishment, lynching, debt peonage, and the convict lease system. A staunch defender of the Liberty and Republican parties, Douglass held several political appointments, frequently corresponded with leading politicians, and advised Presidents Lincoln, Grant, Hayes, Garfield, and Harrison. He met with John Brown before his abortive raid on Harpers Ferry, helped to recruit African American troops during the Civil War, attended most national Black conventions held between 1840 and 1895, and served as U.S. ambassador to Haiti.